Effects of Warm Laser Peening on Thermal Stability and High Temperature Mechanical Properties of A356 Alloy - Hansong Chen; Jianzhong Zhou; Jie Sheng; Xiankai Meng; Shu Huang; Xiaojiang Xie (Metals, 2016)
To study the effects of warm laser peening (WLP) on the thermal stability and mechanical properties of A356 alloy, the samples were treated by WLP using a Nd:YAG solid-state laser and temperature control device. The residual stress, micro-hardness and microstructures of samples treated by WLP were observed. The result shows that the temperature significantly affects the strengthening effect of laser peening (LP). The residual stress induced by WLP decreases with the increasing temperature. The micro-hardness and dislocation density increase first, and then decrease with the increases of temperature. The grain refinement degree of the samples treated by WLP is much higher than that of LP. In addition, after aging for 100 min at 220 °C, the samples treated by LP and WLP were comparatively investigated in thermal stability. Obviously, the residual compressive stress, micro-hardness and microstructure induced by WLP present a better thermal stability property than that of LP. The residual stress and micro-hardness of WLP samples are obviously improved, and the increasing degrees are 23.31% and 19.70%, respectively. The dislocation density remains at a high level, while the grains are still in fine crystalline state.